2004
DOI: 10.1161/01.cir.0000140258.09964.19
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Reentry as a Trigger to Initiate Ventricular Fibrillation During Early Acute Myocardial Ischemia

Abstract: Background-Phase 2 reentry caused by heterogeneous loss of the transient outward potassium current (I to )-mediated epicardial action potential (AP) dome can produce a closely coupled R-on-T extrasystole leading to ventricular fibrillation (VF) under conditions of ST-segment elevation unrelated to ischemia. The present study examined the role of phase 2 reentry in the initiation of VF during early myocardial ischemia. Methods and Results-Regional myocardial ischemia was produced in an isolated, arterially perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 34 publications
2
78
0
3
Order By: Relevance
“…Loss of the action potential dome giving rise to "true" ST-segment elevation and closely coupled phase 2 reentrant extrasystoles may more likely develop within the border zone of the ischemic region [26] or during low-flow ischemia, conditions at which K + accumulation leading to membrane depolarization and thus to a reduction of the Epi notch (due to inactivation of I to ) and slowing of conduction (due to inactivation of I Na ) is minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of the action potential dome giving rise to "true" ST-segment elevation and closely coupled phase 2 reentrant extrasystoles may more likely develop within the border zone of the ischemic region [26] or during low-flow ischemia, conditions at which K + accumulation leading to membrane depolarization and thus to a reduction of the Epi notch (due to inactivation of I to ) and slowing of conduction (due to inactivation of I Na ) is minimized.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that a prominent I to is important in physiological and pathophysiological process (37)(38)(39)(40)(41). The high incidence of phase 2 reentry and ventricular fibrillation during myocardial ischemia was partly due to the prominent I to -mediated epicardial AP dome (42). In patients with coronary heart disease, the incidence of sudden mortality in men was significantly higher compared with that in women (43,44).…”
Section: Discussionmentioning
confidence: 87%
“…Numerous ionic currents, calcium cycling, signal transduction, and so forth would be altered during the myocardial ischemia but, both channelopathy and ischemia may share common mechanisms which result in such prominent J waves and coved type ST elevation, which may be risk factors which develop into ventricular fibrillation due to phase 2 reentry (8,13,18,19).…”
Section: Discussionmentioning
confidence: 99%